YOUTUBE SENI KOMUNIKASI DAKWAH DAN MEDIA PEMBELAJARAN - Guntur Cahyono; Nibros Hassani (Jurnal Al-Hikmah: Jurnal Dakwah, 2019)
This research describes the development of Social Media YouTube that gives new communication pattern for the preacher and the teacher. YouTube is the most strategic media which containing videos content that spreading the information as an art of communication which envolve the users. The society routine for Revolutional Industry 4.0 has changed the communication pattern to get online information (in the internet). Through certain keywords, YouTube users can get the information that is wanted. Media social platform possess the vary contents including Islamic Da’wah and Islamic Education. YouTube in the context of Islamic Education some certain of da’wah contents can become as learning media or material enrichment that is still limited in text book learning present day. [Penelitian ini mendiskripsikan bahwa perkembangan media sosial YouTube memberikan pola baru komunikasi para pendakwah dan guru. YouTube adalah media paling strategis, yang memuat konten video untuk menyebarkan informasi sebagai seni berkomunikasi dengan melibatkan para pengguna. Kebiasaan masyarakat di era revolusi industri 4.0 mengubah pola komunikasi untuk mendapatkan informasi daring (dalam jaringan). Melalui kata kunci tertentu pengguna YouTube bisa memperoleh informasi yang diinginkan. Platform media sosial memiliki konten yang bermacam-macam termasuk didalamnya adalah dakwah Islam dan pendidikan Islam. YouTube Dalam konteks pendidikan Islam beberapa konten dakwah bisa dijadikan sebagai media pembelajaran atau pengayaan materi yang selama ini masih terbatas pada buku pelajaran]. Kata Kunci : YouTube, Komunikasi Dakwah, Media Pembelajaran